The Role of Internal and External Factors on the Success of Surabaya City MSMEs - Gunawan, Florencia; Nathasya, Sri (Gorontalo Development Review, 2024)
This study aims to find out the influence of external factors and internal factors on the success of MSMEs in Surabaya City. The sampling technique uses purposive sampling. The respondents of the study were 70 MSMEs in Surabaya. Data collection techniques use questionnaires that are shared via google form or QR code scan. The analysis tool uses multiple linear regression with the help of SPSS to process the data. The results of the study found that external factors and internal factors have a positive and significant influence on the success of MSMEs in Surabaya City.